Case Study on Nurse Care for Covid-19 Patients with MDRO (Multiple Drug Resistent Organism) in Isolation Intensive Care Unit, Bali Mandara Hospital - Ni Putu Rastiti; Ni Made Garnis Dolesgit; Ni Nyoman Yunita Kartika Dewi (KHD-Production, 2022)
Covid-19 pandemic has made major changes in human civilization. Nurse care becomes more complex for Covid-19 patients who also confirmed with MDRO. MDROs are bacteria resistant to three or more antimicrobials from different classes. This study aims is to know nurse care of patients with Covid-19 and MDRO.The design of this study is qualitative method (case study). The subjects were two patients with Covid-19 and MDRO in Isolation Intensive Care Unit. Data collection techniques were physical and supporting examination, medical record review. Data from the analysis were written descriptively. Priority nursing diagnoses was impaired gas exchange related to ventilation-perfusion imbalance characterized by dyspnea, decreased consciousness. The patient is attached to a VC SIMV mode ventilator. After being treated in Isolation intensive care unit for approximately 14 days, the patient was able to breathe spontaneously with an O2 nasal cannula. The conclusion is nurse care for COVID-19 patients with MDRO is carried out based on isolation precautions (droplet and contact transmission). Nurses are expected to provide professional nurse care to Covid-19 patients with MDRO so the quality of care remains up to standard even during pandemic.